Concept of Arabic Language Learning Management Strategy in Madrasah - Ramadani, Cici; Sutriyani, Sutriyani (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2023)
Arabic language learning management strategy will be explained in this study. The purpose of this study is to examine and discuss the actual concept of Arabic language learning strategy. The aspects that will be described are as follows: 1) definition of Arabic language learning strategy, 2) function of Arabic language learning strategy, 3) types of strategies in Arabic language learning, 4) learning scope, 5) learning management. This study was designed by applying a descriptive qualitative study approach. Data were obtained from books on the concept of Arabic language learning strategy. The data were analyzed by observing the library by searching and collecting books or references related to this discussion. Based on the results, 1) Arabic language learning strategy are rules, plans and steps in the process of learning activities to realize the goals of Arabic language learning, 2) Arabic language learning strategy functions to prepare material and assist students in mastering the language, 3) Arabic learning scope includes: understanding, goals and principles of Arabic language learning, 4) learning management related to readiness in learning.